2020
DOI: 10.1101/2020.12.28.424613
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Squid: Simplifying Quantitative Imaging Platform Development and Deployment

Abstract: With rapid developments in microscopy methods, highly versatile, robust and affordable implementations are needed to enable rapid and wide adoption by the biological sciences community. Here we report Squid, a quantitative imaging platform with a full suite of hardware and software components and configurations for deploying facility-grade widefield microscopes with advanced features like flat field fluorescence excitation, patterned illumination and tracking microscopy, at a fraction of the cost of commercial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 146 publications
1
35
0
Order By: Relevance
“…Pysero also enables visualization and interpretation of antibody responses. The data we report were acquired on Scienion plate reader and Nautilus, a plate reader designed with low-cost components to increase accessibility to this technology (34). Thus, this platform is usable by a large range of research and public health studies.…”
Section: Introductionmentioning
confidence: 99%
“…Pysero also enables visualization and interpretation of antibody responses. The data we report were acquired on Scienion plate reader and Nautilus, a plate reader designed with low-cost components to increase accessibility to this technology (34). Thus, this platform is usable by a large range of research and public health studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the many advantages of smFRET, it is not widely used outside of specialist labs due to the high costs of commercial instruments and a lack of simple, self-build alternatives. A growing trend towards development of low-cost opensource microscopy is taking place and other platforms have recently emerged, including Planktonscope 17 , OpenFlexure Microscope 18 , Flexiscope 19 , miCube 20 , liteTIRF 21 , and Squid 22 . Herein the study describes the protocol for using the smfBox, a recently developed cost-effective confocal set-up capable of measuring the FRET efficiency between two dyes on freely diffusing single molecules.…”
Section: Introductionmentioning
confidence: 99%
“…9 The application of machine learning algorithms in microscopy image analysis potentially helps to find correlations in data with previously trained networks 10,11 or in a completely unsupervised manner. 12 Notable are projects aimed at segmenting cells in micrographs tracking morphological changes, 13 improving the signal-to-noise ratio to enable low-photon dose imaging 14, 15 16,17 or even performing augmented microscopy tasks.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the modern bio-lab, many research groups have already shown that different do-it-yourself (DIY) hardware can also be applied to biological questions and that it is even possible to build customized solutions using 3D printing and electronic setups, which significantly simplify the laboratory process. 13,[20][21][22][23][24][25] Nevertheless, it is worth noting that the inhibition threshold for replication is still too high. After all, it requires a broad knowledge of electronics, 3D design and printing, programming and the subsequent frustration-dominated assembly of the devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation